The Effectiveness of E-LKPD Folktale Material in Instilling Character Values in Class V Students of Madrasah Ibtidaiyah - Putri Calista Arinda; Muhaiminah Jalal; Vioni Saputri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to determine the effectiveness of the E-LKPD on folklore material in instilling character values in fifth-grade students at MIN 4 Muaro Jambi. This research uses the Research and Development (R&D) method with a 4D development model, which includes the stages of define, design, develop, and disseminate. Research data were obtained through teacher response questionnaires and observations during the learning process. The assessment focused on the level of effectiveness of the E-LKPD, which includes aspects of material content feasibility, benefits to learning, and the instillation of character values. The results of the study showed that the E-LKPD obtained an average score of 3.78 with a feasibility percentage of 94.44%, falling into the very effective category. The use of the E-LKPD can support students' understanding of folklore material through the presentation of systematic, attractive, and interactive material, thereby increasing students' interest, motivation, and activeness in learning. The observation results show the implementation of character values in students, such as gratitude, humility, and the ability to respect themselves and their friends. Understanding of character values is also reflected in students' answers on the E-LKPD, which demonstrate the ability to identify and apply character values in daily life. The conclusion of this study shows that the E-LKPD on folklore material is very effective for use in fifth-grade Indonesian language learning.